Why so few EVs are in Kuwait and how to amend it - Ottesen, Andri; Banna, Sumayya (International Journal of Engineering and Technology, 2021)
The automotive industry is at a crossroad. Electric Vehicles (EV) now pose an existential threat to the Internal Combustion Engine (ICE). In some Northern European nations over 50% of new cars sold are EVs, owing in large part to substantial financial incentives to buy and own an EV, such as tax discounts when purchasing an EV, fuel savings, and preferential use of transportation infrastructure. These countries have pledged to cease all imports of non-EVs by 2035. On the other end of the spectrum are Gulf Cooperation Council (GCC) countries, where EVs account for less than 1 percent of vehicles on the road, due in large part to financial and non-financial impediments to buying and owning an EV. In addition, the price per kilometer driven in the GCC is considerably lower with gasoline than with electricity, which contradicts the European experience where cost savings from electricity versus gasoline can be around 8 to 1. Furthermore, as there is an absence of purchase and ownership/utilization taxation of vehicles in the GCC, no tax discount can be levied, in contrast to the EV tax incentives common in Europe. This paper explores which qualities of driving and owning an EV in the GCC are necessary to persuade certain kinds of new automobile consumers to pay a higher purchasing price for owning an EV as opposed to an ICE, in spite of higher costs for electricity compared to gasoline per kilometer driven. This pilot study attempts to provide an insight to new car purchasing behavior among consumers in Kuwait via a qualitative innovative approach known as â€˜Q Methodologyâ€™. Interestingly, the factors that emerged from the research represent three subjective perspectives of new car purchase in Kuwait which were labeled as Factor 1, â€˜Value Seekerâ€™; Factor 2, â€˜Safety Seekerâ€™; and Factor 3, â€˜Performance Seekerâ€™. The study concludes that given financial constraints, the â€˜Value Seekerâ€™ group is not likely to become an early adopter of EVs in the GCC region. Conversely, the â€˜Performance Seekerâ€™, which includes mainly younger men who are more likely to view the fast acceleration of EVs as a deciding factor, and the â€˜Safety Seekersâ€™, who are mainly younger women who would value the environmental aspects of EVs as well as the quiet driving experience and low maintenance requirements are determining factors for EV adoption in the GCC region in the future.Â Â